Hubungan Usia, Jenis Kelamin, Status Imunisasi dan Gizi dengan Kejadian Pneumonia pada Baduta - Elza Nur Fitriyah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Pneumonia is the leading cause of death among children under five years of age in the world. Based on Riskesdas 2007, in Indonesia the percentages of infants and children under five years who died due to pneumonia were 23.8 percent and 15.5 percent respectively. Using a non-reactive unobstructive method, this study aimed at analyzing the relationship between nutrition and the immunization status and the incidence of pneumonia among children under two years old. This study employed secondary data of Laporan Bulanan Kesehatan Ibu dan Anak dan Laporan Gizi (monthly reports of maternal care, child wellbeings, and nutritions) at Bulak Banteng primary health center in the year of 2015. The sample in this study was 604 children under two years selected using a simple random sampling method. The data was obtained by collecting data of children under two years and the incidence of pneumonia among children under two years at Bulak Banteng health center in 2015. Using a bivariate analysis, it showed that there was relationship between variables of age, sex, immunization, and nutritional status, and the incidence of pneumonia. The p value and OR variables used respectively are 0.00 OR 3.6; 0.00 OR 1.6; 0.00 OR 3.2 and 0.00 OR 16.6. The conclusion of this study is that there was a significant relationship between the variables of age, sex, immunization, and nutritional status and the incidence of pneumonia among children under two years. The advice to primary health centers is to give PMT (additional nutritious food) to children under two years without good nutritional statuses and to monitor the health status of patients who have pneumonia with home visits to avoid recurrence.